Research of fast inter-AP handoff algorithm - HAN Xiaoyu; HUANG Tinglei; LIN Ke (Gong-kuang zidonghua, 2014)
In view of problem that traditional underground cable scheduling system cannot meet mobility requirements, a fast inter-AP handoff algorithm applied in intelligent scheduling and management system for mine locomotive was put forward. The algorithm divides coverage area of access point, and uses the master interface and slave interface for communication and connection respectively, which effectively reduces time delay for terminal to switch between different wireless access points. The experimental results show that the algorithm can effectively reduce handoff latency, and it also has good performance when the signal is unstable.